2003
DOI: 10.1002/cem.824
|View full text |Cite
|
Sign up to set email alerts
|

Peak alignment using reduced set mapping

Abstract: This paper presents an algorithm and method for peak alignment or spectral synchronization of firstorder data with pronounced differences between baseline and signals of interest, e.g. data typically acquired by NMR, MS, GC, LC and CE. The method preserves the shapes of peaks, merely altering their positions on the x-axis of the data set. The method involves coarse discrimination between baseline and peaks, generation of a sparse vector or a list representing peak maximum positions, and analysis of the vector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
77
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 22 publications
0
77
0
1
Order By: Relevance
“…Previous studies have shown that the variation of peak location in different data sets is nonlinear [21], [10]. The example in [28] shows that this variation still exists even when we use technical replicates.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Previous studies have shown that the variation of peak location in different data sets is nonlinear [21], [10]. The example in [28] shows that this variation still exists even when we use technical replicates.…”
mentioning
confidence: 85%
“…Dynamic programming (DP) based approaches [14], [21] have also been proposed. DP has been used in gene expression analysis to warp one gene expression time series to a similar series obtained from a different biological replicate [1], where the correspondence between the two gene expression time series is guaranteed.…”
mentioning
confidence: 99%
“…Alignment approaches either aim at the detection of corresponding peaks among all spectra (cf. [13]) or modify the exact position of peaks for maximization of similarity among all spectra (cf. [14]).…”
Section: Alignment Of Sroismentioning
confidence: 99%
“…2. Other methods include genetic algorithm-based methods (Forshed et al 2002;Lee and Woodruff 2004), partial linear fit (Vogels et al 1996), reduced set mapping (Torgrip et al 2003), and principal component analysis-based methods (Stoyanova et al 2004). One common problem with the existing methods is that they often disregard the existence of noise, which is typically observed in NMR spectra.…”
Section: Introductionmentioning
confidence: 99%